Comparing structural and vascular parameters between advanced pseudoexfoliation glaucoma and primary open angle glaucoma using optical coherence tomography angiography - Yadollah Eslami; Hamed Hosseinikhah-Manshadi; Samaneh Gholamhoseinpour-Omran; Sepideh Ghods; Samin Ghasemi; Seyed Mehdi Tabatabaei (BMC Ophthalmology)
Abstract Background To compare structural and vascular parameters between advanced pseudoexfoliation glaucoma (PXG) and primary open-angle glaucoma (POAG). Methods One hundred and six eyes of 81 patients were enrolled in this cross-sectional study. All patients underwent complete ophthalmic examination and measurement of the thickness of the peripapillary retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC). The vessel densities (VD) in the peripapillary and macular area were also determined using optical coherence tomography angiography (OCTA). A linear mixed model was used for the comparison of the structural and vascular parameters between groups with adjustment for type of glaucoma, age, sex, intraocular pressure (IOP), and mean deviation (MD) of the visual field C24-2. Results The patients in the PXG group were significantly older (68.06 ± 10.6 vs. 61.24 ± 15.23, p = 0.01) and had worse MD in the visual field C24-2 (-24.83 ± 6.18 vs. -22.37 ± 5.94, p = 0.04). Sex and IOP were comparable between groups (p > 0.05). Perippaillry RNFL and GCC thickness were not different between groups (p > 0.05). The PXG eyes showed lower VD in the average peripapillary area (32.67 ± 7.78 vs. 37.75 ± 8.87, p = 0.027) and nasal (37.45 ± 9.74 vs. 42.15 ± 7.36, p = 0.026) and inferior (38.09 ± 8.27 vs. 42.71 ± 9.13, p = 0.041) quadrants of parafovea. Conclusion The advanced PXG and POAG eyes have comparable structural defects in the peripapillary and inner macula while the PXG eyes may have more vascular deterioration, especially in the macula.